The processes of transformation of contemporary cities based on selected examples - Jopek, Dorota (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
Contemporary cities are infl uenced by dynamic spatial transformation related to demographic, social and economic changes. As a result of these factors, the development challenges of urban centers may be extremely different. Some of the cities are subject to a process of depopulation associated with both negative demographic trends and an increase of unemployment and the lack of jobs for young people. The second part of the cities are the centers with better growth potential derived mostly from their historical role in the development of the entire country carried out at various levels. This variety of growth factors is created by the benefi cial impact of the institutions of scientifi c, cultural and private economic sector. The attractiveness of these cities due to an increased and diversifi ed offer on the labor market and better living conditions for their inhabitants is carried out among others by the availability of high-quality public space. In studies of the process of transformation of cities, spatial aspects seem to be less important in the combination of economic, demographic and social aspect. Although its interdependencies evident, however, spatial changes are mostly infl uenced by all of above aspects. Analysis of planning documents and urban development strategy shows that most of the contemporary cities target on the improvement of the quality of life of their residents and the implementation of the principles of sustainable development. In this paper, the author attempts to study the processes of transformation taking place in contemporary cities.